2021
DOI: 10.1038/s41598-021-84356-w
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to SARS-CoV-2 and risk of past or future sick leave

Abstract: The extent that antibodies to SARS-CoV-2 may protect against future virus-associated disease is unknown. We invited all employees (n = 15,300) at work at the Karolinska University Hospital, Stockholm, Sweden to participate in a study examining SARS-Cov-2 antibodies in relation to registered sick leave. For consenting 12,928 healthy hospital employees antibodies to SARS-CoV-2 could be determined and compared to participant sick leave records. Subjects with viral serum antibodies were not at excess risk for futu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…In agreement with our results, many studies have reported an increased risk of exposure to SARS-CoV-2 among HCWs [ 19 ], in elderly care homes [ 12 , 15 , 20 ], nursing facilities [ 16 ] as well as among the HCWs at hospitals [ 17 , 18 , 21 ]. Seropositivity was comparable to observational studies from hospitals in the same region and near in time [ 11 , 18 ]. Participating in the active care of COVID-19 patients was a significant risk factor for being seropositive.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In agreement with our results, many studies have reported an increased risk of exposure to SARS-CoV-2 among HCWs [ 19 ], in elderly care homes [ 12 , 15 , 20 ], nursing facilities [ 16 ] as well as among the HCWs at hospitals [ 17 , 18 , 21 ]. Seropositivity was comparable to observational studies from hospitals in the same region and near in time [ 11 , 18 ]. Participating in the active care of COVID-19 patients was a significant risk factor for being seropositive.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, it is important to efficiently detect and manage healthcare-related SARS-CoV-2 exposures. We have previously found that presymptomatic infection can be readily detected by SARS-CoV-2 antibody screening and SARS-CoV-2 RT-PCR testing [ 10 , 11 ]. Seropositive HCW have no excess risk for disease in the coming months [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previously described Stockholm HCW cohort, all healthcare providers in the capital region of Sweden were asked about participation in a study of past or present SARS-CoV-2 infections [ 8 , 9 ]. Among the major healthcare providers who agreed to participate, a very high proportion (>90%) of the HCWs at work were enrolled, following written informed consent [ 8 , 9 ]. This report focuses on the two largest healthcare providers, Karolinska University Hospital and Stockholm South General Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The Stockholm HCW study of past or present SARS-CoV-2 invited all healthcare workers (HCWs) in the region for PCR and antibody testing in April-June 2020, with about 27,000 HCWs enrolled [ 7 9 ]. Whereas antibodies and low amounts of virus in PCR (high Ct values) were associated with past disease (post-symptomatic subjects) [ 7 , 8 ], high amounts of virus in PCR predicted future disease in the next 1–2 weeks [ 7 ]. The pattern with no symptoms, high amounts of virus and no antibodies was unfortunately particularly common among HCWs working with home care for older persons [ 10 ].…”
Section: Introductionmentioning
confidence: 99%